Limitations of Technical Approaches to Transport Planning Practice in Two Cases: Social Issues as a Critical Component of Urban Projects. (1st January 2020) - Mottee, Lara K.; Arts, Jos; Vanclay, Frank; Howitt, Richard; Miller, Fiona
ABSTRACT: Technical transport models are commonly relied upon in planning practice for the development of urban rail infrastructure projects. By considering the assessment and management of social impacts in the planning and decision-making of two rail megaprojects (the North-South Metro line in Amsterdam, the Netherlands, and the Parramatta Rail Link in Sydney, Australia), we found that technical approaches continued to overlook social impacts, and had an overemphasis on economic and engineering considerations. We conclude that good practice Social Impact Assessment (SIA) offers opportunities to better consider social issues as a critical component of transport projects.